2018
DOI: 10.3126/nelta.v23i1-2.23358
|View full text |Cite
|
Sign up to set email alerts
|

Using technology in teaching English at the S.S.C. level

Abstract: In this an era of technology, new technologies particularly computer, multimedia, mobile phone and the internet offer possibilities for overcoming geographical and cost barriers in teaching and learning. This study attempts to trace the use of technology in teaching English at the S.S.C. (Secondary School Certificate) level in Bangladesh. It also focuses on the impact of using technology in teaching and learning English. Eight teachers and 60 students from four private schools in Dhaka city were selected to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Google Meet as a modern application has a significant impact on learning, specifically the Academic Writing Course. Singhal stated in Ullah and Farzana (2018) that the use of technology and learning English are inextricably linked. This study's findings are similar to those of Pernantah et al (2021), who discovered that using the Google Meet application is easier and more effective in delivering online learning materials.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Google Meet as a modern application has a significant impact on learning, specifically the Academic Writing Course. Singhal stated in Ullah and Farzana (2018) that the use of technology and learning English are inextricably linked. This study's findings are similar to those of Pernantah et al (2021), who discovered that using the Google Meet application is easier and more effective in delivering online learning materials.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…The use of this application as a technology used in the teaching and learning process in a classroom will attract and motivate students to learn. Ullah & Farzana (2018) found that in technology-affiliated classes, most students felt comfortable, but they needed time to take a class with the help of technology. Therefore, it needs further investigation, particularly in the effort to gain some English vocabulary.…”
Section: Toontastic Application and Its Advantagesmentioning
confidence: 99%
“…Technology use in teaching and learning, as well as all other aspects of modern life, is now required and cannot be avoided. Using technology in teaching and learning has grown ingrained (Ullah & Farzana, 2018). In addition to facilitating the learning process, the use of technology by teachers in the classroom inspires and supports student achievement (Phung, 2021;Mohan & Ismail, 2021;and Rojabi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, challenges exist in the effective integration of ICT in English language education. While there are opportunities for ICT in language teaching, such as providing rich authentic learning materials and overcoming the lack of authentic language environment (Ullah & Farzana, 2018), there are also challenges related to access to ICT tools and the necessary skills for their effective use (Poudel, 2022). Furthermore, the utilisation of available ICT resources in English language teaching and learning is often found to be unsatisfactory, despite teachers possessing the necessary ICT skills (Samuel & Zaitun, 2007).…”
Section: Introductionmentioning
confidence: 99%